2017
DOI: 10.1371/journal.pone.0169223
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Pre-Pregnancy Obesity Is Associated with Altered Placental Transcriptome

Abstract: Maternal obesity has a major impact on pregnancy outcomes. There is growing evidence that maternal obesity has a negative influence on placental development and function, thereby adversely influencing offspring programming and health outcomes. However, the molecular mechanisms underlying these processes are poorly understood. We analysed ten term placenta’s whole transcriptomes in obese (n = 5) and normal weight women (n = 5), using the Affymetrix microarray platform. Analyses of expression data were carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 48 publications
3
40
0
Order By: Relevance
“…Another mechanism by which maternal obesity may affect the neurodevelopment of offspring may be related to insulin resistance, which contributes to abnormal central glucose metabolism and transport. One study[ 46 ] analyzed the whole placental transcriptome in obese and normal-weight women and showed that maternal obesity had a negative effect on placental development and function. Another study[ 47 ] used oxidative stress biomarkers to analyze samples from mothers and offspring and found that maternal obesity could affect the maternal microenvironment and that oxidative stress has a negative impact on the placenta and fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism by which maternal obesity may affect the neurodevelopment of offspring may be related to insulin resistance, which contributes to abnormal central glucose metabolism and transport. One study[ 46 ] analyzed the whole placental transcriptome in obese and normal-weight women and showed that maternal obesity had a negative effect on placental development and function. Another study[ 47 ] used oxidative stress biomarkers to analyze samples from mothers and offspring and found that maternal obesity could affect the maternal microenvironment and that oxidative stress has a negative impact on the placenta and fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…A successful pregnancy involves complex interactions between the immune cells residing at the maternal-fetal interface 108 and circulating maternal factors that could culminate into secretion of immune mediators into fetal circulation. 109,110 During the first trimester, the placenta enables the establishment of pregnancy, providing physical support and immunologic tolerance to the developing embryo. 111 As gestation progresses, the placenta takes over the roles of facilitating gas exchange as well as the transfer of nutrients, waste products, hormones, and other immune mediator that support fetal growth and impact development and maturation of the offspring immune system.…”
Section: Pregravid Obesity and Inflammation At The Maternal-fetal Intmentioning
confidence: 99%
“…The fetal portion of the placenta is called the villous chorion, which allows for the transfer of nutrients from maternal blood to fetal circulation. A successful pregnancy involves complex interactions between the immune cells residing at the maternal–fetal interface and circulating maternal factors that could culminate into secretion of immune mediators into fetal circulation . During the first trimester, the placenta enables the establishment of pregnancy, providing physical support and immunologic tolerance to the developing embryo .…”
Section: Introductionmentioning
confidence: 99%
“…Changes in placental function are thought to be pivotal in the development of pregnancy complications [10,11] and could also be a key link between the maternal and intrauterine milieu and long-term health of the offspring [12,13]. Alterations in placental function and structure in response to obesity and their underlying molecular mechanisms have been explored both in humans and in animal models [9,[14][15][16][17]]. Yet, even though fetal growth restriction (FGR) is recognized as a placenta-related disorder [18], the impact of maternal obesity on the placental transcriptome in this context remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%